Family formation, fatherhood and crime. An invitation to a broader perspective on crime and family transitions - Torbjørn Skarðhamar; Torkild Hovde Lyngstad (Statistics Norway, Research Department, 2009)
Using large-scale individual-level Norwegian administrative register data on the total population of men, we study the offending rates five years prior to and after five different family-related transitions. Leading criminological theories predict that marriage and fatherhood has a preventive effect on crime, with marriage receiving most support by empirical research. The last decades' major changes in family patterns warrant a re-examination of the marriage effect. We argue that marriage, cohabitation, and fatherhood all are important aspects of the family formation process. We find some support for the hypothesis that family formation inhibit criminal behaviors, but our results are less clear-cut than those reported by previous research. Most importantly, the declines in offending in the years prior to experiencing family transitions do not seem to be of a permanent nature.
Keywords: J1; Z00; 330; crime; desistance; family; fertility; Norway; register data